Selective adsorption of soil humic acid on binary systems containing kaolinite and goethite: Assessment of sorbent interactions. (11th April 2019) - Chen, Hongfeng; Koopal, Luuk K.; Xu, Jinling; Wang, Mingxia; Tan, Wenfeng
Abstract : Inorganic colloids are ubiquitous in soils and coexist as simple mixtures or as strong associations of particles. The coexisting inorganic colloids with a variety of active sites can selectively adsorb humic substances and thus affect the availability and mobility of organic matter. To investigate the selective adsorption of organic matter by coexisting inorganic colloids, humic acid (JGHA) extracted from soil, a kaolinite and goethite synthetic association (KGA) and a kaolinite and goethite mixture (KGM) were prepared and studied. With the adsorption expressed in μmol m −2, the adsorption affinity of JGHA on KGA (initial slope of isotherms) was slightly higher than that on KGM, although KGM could adsorb more JGHA molecules at larger JGHA concentrations. At pH 4, JGHA was adsorbed on the kaolinite edges and goethite through electrostatic attraction and ligand exchange, and on the kaolinite siloxane plates through hydrophobic interaction. At pH 6 and 8, the adsorption occurred only on the kaolinite siloxane plates and goethite. The overall average adsorption Gibbs energies were moderately negative, and comprised a strongly negative average overall molar entropy and a negative average overall molar entropy contribution. Thus, overall JGHA adsorption on KGA and KGM was enthalpy controlled. The large exothermic enthalpy gains and entropy losses were a result of electrostatic attraction and ligand exchange. The entropy gains because of hydrophobic attraction between JGHA and the kaolinite siloxane plates are masked by the larger entropy loss of adsorption on the hydrophilic surfaces. The fractions of JGHA with molar mass > 12.9 kDa (1 Da = 1 g mol −1 ) were adsorbed selectively by KGM, whereas the fractions < 12.9 kDa were selectively adsorbed by KGA. High molar mass and hydrophobic fractions adsorb selectively on the kaolinite siloxane plates, whereas low molar mass fractions with hydrophilic groups adsorb selectively on goethite and the kaolinite edges. Highlights: Selective adsorption behaviour of HA on binary systems containing kaolinite and goethite. High molar mass and hydrophobic HA fractions selectively adsorb on kaolinite siloxane plates. Low molar mass and hydrophilic HA fractions selectively adsorb on kaolinite edges and goethite. Binding affinity of HA to KGA is stronger than to KGM; mineral associations are more beneficial for fixing OM in soil.